2009
DOI: 10.1038/nn.2459
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin 1 accelerates synaptogenesis in hippocampal neurons through neuroligin 1

Abstract: In cultured rat hippocampal neurons, we found that thrombospondin 1 (TSP1) increased the speed of synapse formation in young neurons, but not the final density of synapses in mature neurons. TSP1 interacted with neuroligin 1 (NL1) and application of the NL1 extracellular domain blocked TSP1-induced synaptogenesis. Furthermore, knocking down endogenous NL1 inhibited TSP1's effect. Our results indicate that TSP1 accelerates the speed of synaptogenesis through NL1 in hippocampal neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
154
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(158 citation statements)
references
References 13 publications
1
154
1
2
Order By: Relevance
“…These findings suggested that NLs require other extracellular ligands besides neurexins. Two proteins, PTPRT and thrombospondin-1, have been reported to regulate synapse formation via direct interactions with NLs in cultured hippocampal neurons (39,40). However, because PTPRT is localized specifically to excitatory synapses, and the localization of thrombospondin-1 at synapses remains unclear, these findings cannot account fully for isoform-dependent differential NL activities in synapse validation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that NLs require other extracellular ligands besides neurexins. Two proteins, PTPRT and thrombospondin-1, have been reported to regulate synapse formation via direct interactions with NLs in cultured hippocampal neurons (39,40). However, because PTPRT is localized specifically to excitatory synapses, and the localization of thrombospondin-1 at synapses remains unclear, these findings cannot account fully for isoform-dependent differential NL activities in synapse validation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, other studies report that abnormal spine density at young ages is rectified at more mature ages (for recent examples see Refs. 71,72). Accordingly, spine density is regulated by several powerful mechanisms that ensure normal density at the adult stage if at all possible.…”
Section: Discussionmentioning
confidence: 99%
“…Dock4 scramble shRNAs or shRNAs were subcloned to the lentiviral vector pFUGW, which contains a GFP coding sequence separated by an internal ribosome entry site. pFUGW shRNAs were transfected into HEK293T cells together with an HIV-1 packing vector ⌬8.9 and a vesicular stomatitis virus glycoprotein (VSVg) envelope plasmid to generate lentiviral particles as described previously (33).…”
Section: Methodsmentioning
confidence: 99%